The League of Nations and the Mexican detachment problem: the international mission of Julian Nogueira in Mexico, August-September 1923 (Tzintzun, Revista de Estudios Históricos, 2016)
The stay in Mexico by Julian Nogueira, high official of the League of Na-tions, was the first formal and lasting contact between this internationalorganization and the absent revolutionary country. During his stay, hewould inquire into the Mexican political means to estimate the validityof the arguments justifying the distance from Geneva. He also carried outextensive propaganda work among key figures of the revolution, mediaand internationalists who years later would have an outstanding perfor-mance in the history of Mexico in the League of Nations, with the premisethat the lack of understanding about the mission and activities of the or-ganization from Geneva was the basis of the Mexican rejection.
Keywords: Leagua of Nations; Julian Nogueira; interwar period; Bucareli agreements; Regis d'Oliveira